Characterization of Water-Soluble Complexes of Polyacrylic Acid with α-Amylase from Aspergillus oryzae - Altikatoglu, Melda; Tavukcuoglu, Oezlem; Mustafaev, Mamed (SPRINGER, 2010)
Polycomplex formation of alpha-Amylase from Aspergillus oryzae (TAKA) with polyacrylic acid (PAA) was studied by pH titration, fluorescence, and high performance liquid chromatography (HPLC) methods in water solutions. Acording to the our results, the complex formation and its solubility were depended on nature of enzyme and the pH of solutions. Both of them correlates isoelectric points (PI). The stability of PAA-amylase complexes was negligibly weak at pH 7 [pH > pI (isoelectric pH)]. Stable water-soluble polycomplexes were formed at pH 5 (pI similar to 4.5) and coexisted with free protein molecules. Insoluble complexes has been observed at pH < 4.5. The frozen storage stabilities of the obtained complexes were also studied by measuring the activities at different pH.
Keywords: Polyelectrolytes; Enzyme; HPLC; Fluorescence; Stabilization; BOVINE SERUM-ALBUMIN; POLY(ACRYLIC ACID); TRYPTOPHAN; BINDING; RESOLUTION; Biochemistry & Molecular Biology